Kualitas hidup pada ibu dari anak dengan attention deficit hiperactivity disorder - Sofia Nurinawati; Fredrick Dermawan Purba; Laila Qodariah (University of Muhammadiyah Malang, 2021)
Having an attention deficit hyperactivity disorder (ADHD) child is certainly not easy in her care. Mother, as the most dominant figure in her parenting, certainly experienced psychological impact. This study aims to describe the experience of mothers who are parenting with ADHD related to their quality of life. This research is qualitative research with a Phenomenological approach. The study participants consisted of 5 mothers of children with ADHD aged 36-45 years. Data retrieval is done using semi-structured interviews. Data analysis using thematic analysis. The quality of life in mothers of children with ADHD can be described through 23 themes divided into four domains of quality of life: physical, psychological, social, and environmental. In the physical domain, parenting with ADHD affects daily activities that cause mothers to feel tired. In the psychological domain, the mother feels a variety of feelings from the beginning of the diagnosis to during parenting. In the social relation domain, parenting with ADHD affects maternal relationships. In the environment domain, some costs need to be incurred for the child. Mothers are also able to get new information and lessons during parenting with ADHD.